1995
DOI: 10.1136/fn.73.1.f8
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight infants and total parenteral nutrition immediately after birth. II. Randomised study of biochemical tolerance of intravenous glucose, amino acids, and lipid.

Abstract: This randomised study aimed to compare the biochemical tolerance of three parenteral regimens administered during the first 48 hours of life. Twenty nine infants were randomised to either: (a) glucose 10%; (b) glucose 100/o/amino acids; (c) glucose 100/olamino acids/lipid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 30 publications
(7 reference statements)
3
25
0
1
Order By: Relevance
“…14 This might be related to the stimulating effect on the insulin secretion that the early introduction of amino acids produces. 15 In VLBW premature infants, the incidence of hyperglycemia is frequent because the endogenous production of glucose is not suppressed either by the exogenous intakes of nutrients or by the infusion of lipids. 16 Plasmatic values of triglycerides in the aggressive group were in the normal range, similar to that found by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…14 This might be related to the stimulating effect on the insulin secretion that the early introduction of amino acids produces. 15 In VLBW premature infants, the incidence of hyperglycemia is frequent because the endogenous production of glucose is not suppressed either by the exogenous intakes of nutrients or by the infusion of lipids. 16 Plasmatic values of triglycerides in the aggressive group were in the normal range, similar to that found by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that starting protein within 4 hours of birth (in the form of intravenous [IV] amino acids [AAs] in PN) is associated with enhanced blood glucose control and reduced insulin use in very preterm infants 12 . Although the exact mechanism for this effect is unknown, the effect of AAs on insulin secretion is well described in preterm infants 3 , 13 . It is equally well described that some AAs are more potent secretagogues than others.…”
Section: Introductionmentioning
confidence: 99%
“…During the first week of life, the three infants had high glucose requirement; ≥7–8 mg/kg/min is practically diagnostic of hyperinsulinism . It is well known that early administration of amino acids enhances endogenous insulin secretion . Since we routinely provided preterm infants with early aggressive intravenous nutrition, most of them required a glucose infusion rate of 7–10 mg/kg/min to maintain normoglycemia during the first days of life.…”
Section: Discussionmentioning
confidence: 99%